Physical and biological studies on DNA/anti-DNA immune complex formed in vitro - Gao, Yuehua (Kluwer Academic Publishers, 1997)
In vitro preparation of DNA/anti-DNA immune complex using monoclonal antibody and low molecular weight homogeneous DNA was described and the characteristics of the immune complex were identified. The immune complex was formed by the monoclonal antibody with DNA effectively at high ratios of antibody/DNA. The activation and binding ability of the immune complex to the complement was considerably high, whereas the capacity to bind red blood cells via C3b complement component receptor was shown relatively low. The assay of sucrose density gradient ultracentrifugation indicated that the sedimentation coefficient of the immune complex was between 10S and 23S. Studies of organ distribution and uptake of IC demonstrated a particular affinity to the kidney tissue. The significance of these results with respect to the latent pathogenicity of the immune complex was discussed.